Milker’s nodules: Classic histological findings - Espósito, Ana Cláudia Cavalcante [UNESP]; Jorge, Marilia Formentini Scotton [UNESP]; Marques, Mariângela Esther Alencar [UNESP]; Abbade, Luciana Patrícia Fernandes [UNESP] (FapUNIFESP (SciELO), 2017)
Milker’s nodule is an occupational dermatovirose caused by Parapoxvirus, which is self-limited and, due to the lack of information of health professionals, may lead to underdiagnosis. We present two cases with exuberant manifestations and classic histopathologic findings. Case 1: Male, 19 years of age, milker, presented nodules and blisters on his palm for 15 days. Case 2: Male, 33 years of age, administrative assistant, presented erythematous nodules on his palms with lymphangitis for 5 days. He had milked a cow one week before the onset of the lesions. In both cases, the histopathology was representative and coincident with the clinical hypothesis. The lesions have presented complete involution. Milker’s nodule diagnosis is based on clinical presentation, epidemiology, and histopathology. The knowledge of this disease is essential for its correct diagnosis, as well as to guide the implementation of public health measures and the appropriate treatment of sick cattle.
Keywords: Parapoxvirus; Poxviridae; Poxviridae Infections; Pseudocowpox virus